2001
DOI: 10.1002/pros.10027
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 degradation products modulate epithelial and stromal 5α‐reductase activity of human benign prostatic hyperplasia in vitro

Abstract: The present data on BPH tissue suggest that lysophospholipids may play a specific and structure-related role in the posttranslational regulation of human prostatic 5alpha-reductase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“… 40 Although some previous study indicated that PLA2 activity is increased in CaP cells, 41 PLA2 was also reported to be highly active in BPH, and no significant difference of PLA2 levels in serum was observed between patients with BPH or CaP. 42 , 43 Considering that the conversion of PC from LPC is catalyzed by LPCATs, some previous studies may offer a possible explanation for the elevated PCs/LPC ratio in cancers. In HCC tissues and cells, the PC (16:0/16:1)/LPC (16:0) ratio has been reported to be significantly higher because of the elevated activation of LPCAT1, which is a key enzyme in the PC and LPC remodeling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 40 Although some previous study indicated that PLA2 activity is increased in CaP cells, 41 PLA2 was also reported to be highly active in BPH, and no significant difference of PLA2 levels in serum was observed between patients with BPH or CaP. 42 , 43 Considering that the conversion of PC from LPC is catalyzed by LPCATs, some previous studies may offer a possible explanation for the elevated PCs/LPC ratio in cancers. In HCC tissues and cells, the PC (16:0/16:1)/LPC (16:0) ratio has been reported to be significantly higher because of the elevated activation of LPCAT1, which is a key enzyme in the PC and LPC remodeling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In the Lands' pathway, LPC is produced by the hydrolysis of PC by an enzyme called phospholipase A2 (PLA2), while PC can be produced by the addition of a fatty acid to LPC using LPCATs 40 . Although some previous study indicated that PLA2 activity is increased in CaP cells, 41 PLA2 was also reported to be highly active in BPH, and no significant difference of PLA2 levels in serum was observed between patients with BPH or CaP 42,43 . Considering that the conversion of PC from LPC is catalyzed by LPCATs, some previous studies may offer a possible explanation for the elevated PCs/LPC ratio in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…17β-HSOROX) enzymes involved. 18 For testosterone to be maximally active in the prostate, it must be converted to dihydrotestosterone (DHT) by the enzyme 5α-reductase, 19,20 DHT has a much greater affinity for the androgen receptor than does testosterone which allows it to accumulate in the prostate even when circulating levels of testosterone are low. 21,22 DHT is approximately twice as potent as testosterone in studies of rats at equivalent androgen concentrations.…”
Section: Androgen Metabolism and Bph Developmentmentioning
confidence: 99%